DISTRIBUTION OF TRACE METALS IN WATER, SEDIMENT AND BIOTA FROM IKPUKULU-AMA CREEK PORT HARCOURT, RIVERS STATE, NIGERIA - OKOSEIMIEMA, I.J; VINCENT-AKPU, I.F. (Nigerian Journal of Fisheries, 2020)
The distribution of trace metals (Lead (Pb), Iron (Fe), Copper (Cu), Zinc (Zn) and Cadmium (Cd) were assessed from three stations in water, sediment and biota (Fish and plankton) from Ikpukulu-ama creek in Rivers State, Nigeria from March to August,2017. The physico- chemical parameters in water that affect metal concentrations were analyzed using standard methods and the metals were analyzed using Atomic Absorption Spectrophotometer (AAS) after acid digestion. Concentrations of metals in water were in the order of Cd<Cu<Pb<Zn<Fe, in sediments Cd<Cu<Pb<Zn<Fe, in fish Cd<Cu<Pb<Zn<Fe while in plankton the order of concentration were Cu<Zn<Fe, while Cd and Pb were below detectable limit. The mean concentrations of metals in surface water (mg/L) were 5.2, 0.83, 0.03, 0.46, and 0.01 for Fe, Zn, Cu, Pb and Cd respectively, in sediments (mg/g) the values were 16.0, 0.65, 0.09, 0.32, and 0.01 for the same metals. The mean concentrations of metals in fish (mg/g) were Fe (2.96), Zn (1.87), Cu (0.03), Pb (0.08) and Cd (<0.001), while for plankton (mg/L) were Fe (13.2), Zn (2.09), Cu (0.06), Pb (<0.001) and Cd (<0.001). Trace metal concentrations in water, sediment and biota were below the maximum permissible levels recommended by National standards.